2012
DOI: 10.1088/1674-4527/12/9/003
|View full text |Cite
|
Sign up to set email alerts
|

The Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST)

Abstract: The Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST, also called the Guo Shou Jing Telescope) is a special reflecting Schmidt telescope. LAMOST's special design allows both a large aperture (effective aperture of 3.6 m-4.9 m) and a wide field of view (FOV) (5 • ). It has an innovative active reflecting Schmidt configuration which continuously changes the mirror's surface that adjusts during the observation process and combines thin deformable mirror active optics with segmented active optics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
634
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,324 publications
(673 citation statements)
references
References 43 publications
5
634
0
1
Order By: Relevance
“…LAMOST is a ≃ 4 meter quasi-meridian reflecting Schmidt telescope located at Xinglong Observing Station in the Hebei province of China (Cui et al 2012). It has a field of view of 5 • in diameter and it is exclusively dedicated to obtain optical spectroscopy of celestial objects.…”
Section: The Dr 4 Of Lamostmentioning
confidence: 99%
See 1 more Smart Citation
“…LAMOST is a ≃ 4 meter quasi-meridian reflecting Schmidt telescope located at Xinglong Observing Station in the Hebei province of China (Cui et al 2012). It has a field of view of 5 • in diameter and it is exclusively dedicated to obtain optical spectroscopy of celestial objects.…”
Section: The Dr 4 Of Lamostmentioning
confidence: 99%
“…These were selected as F, G, K stars with northernhemisphere LAMOST (Large Sky Area Multi-Object Fibre Spectroscopic Telescope; Cui et al 2012;Zhao et al 2012) or southern-hemiesphere RAVE (Radial Velocity Experiment; Kordopatis et al 2013) spectra displaying ultraviolet (UV) excess as indicated by their GALEX (Galaxy Evolution Explorer; Martin et al 2005) FUV-NUV colours (where FUV and NUV are the far-UV and near-UV magnitudes) in a T eff vs. FUV-NUV diagram (see Figure 1). This resulted in 430 WD+FGK binary candidates from RAVE DR 1 and 504 candidates from LAMOST DR 1.…”
Section: Introductionmentioning
confidence: 99%
“…The telescope is characterized by both a large field of view and large aperture, with an effective aperture of 3.6-4.9m and 4,000 fibers mounted on its focal plane. Its spectral wavelength ranges from 3800Å to 9000Å and spectral resolution is about R∼1800 (Cui et al 2012. The fourth data release (DR4) of LAMOST includes the pilot survey(2011 October to 2012 June) and the regular survey(2012 September to 2016 June), and will be public released in June 2018.…”
Section: Galaxies In Lamost Dr4mentioning
confidence: 99%
“…In addition to our data, HD 24355 has been observed as part of the LAMOST campaign (Cui et al 2012;Zhao et al 2012) and was made public as part of Data Release 1 (DR1; Luo et al 2015). The LAMOST spectrum was obtained at a resolution of R ∼ 1800, and is shown in Fig.…”
Section: Spectral Classificationmentioning
confidence: 99%